Acceleration of multiply charged ions by a high-contrast femtosecond laser pulse of relativistic intensity from the front surface of a solid target. (May 2016) - Shulyapov, S.A.; Mordvintsev, I.M.; Ivanov, K.A.; Volkov, P.V.; Zarubin, P.I.; Ambrožová, I.; Turek, K.; Savel'ev, A.B.
Abstract: It is shown that the acceleration efficiency of protons and multiply charged ions (and also the charge composition of the latter) accelerated backwards under irradiation of the front surface of thick solid targets by high-power femtosecond laser radiation with an intensity of is determined by the contrast of this radiation. Thus, highly ionised ions up to and are recorded on polyethylene, silicon and molybdenum targets at a contrast of, the ions with charges up to and possessing an energy of more than per unit charge. In the case of a metal target, the acceleration efficiency of protons is significantly reduced, which indicates cleaning of the target surface by a pre-pulse. The measurements performed at a contrast increased by two-to-three orders of magnitude show the presence of fast protons (up to ) on all targets, and also a decrease in the energy and maximum charge of multiply charged ions.